Inhumane Arbeitsbedingungen auf dem globalen Markt: Wer kann, wer soll handeln? - Christoph Scherrer; Rolf J. Langhammer; Jürgen Matthes; Ingo Pies; Peter Seele; Sebastian Knebel (Wirtschaftsdienst, 2013)
Brände in Textilfabriken und Selbstmorde bei Computer-Zulieferern machten jüngst deutlich: In asiatischen Werken, die für den europäischen und amerikanischen Markt produzieren, herrschen teilweise skandalöse Arbeitsbedingungen. Als Maßnahmen gegen diese Missstände werden Sozialkapitel in Handelsabkommen, Gütesiegel und die Selbstverpfl ichtung von Unternehmen diskutiert. Einige der Zeitgesprächs-Autoren geben zu bedenken, dass die Arbeitsbedingungen historisch zu relativieren und im Kontext mit dem dortigen Produktivitätsniveau zu beurteilen seien. – – Workers in Asian factories producing for Western markets suffer under inhumane working conditions. Suicides at Chinese suppliers of computer manufacturers and a fire in a Bangladesh garment factory recently drew public attention to this problem. But would workers in developing countries really benefi t from better working conditions and higher wages? It may be more likely that countries implementing these improvements would lose in global competition. Therefore, developing countries are limited in their ability to raise labour standards on their own. This competitive situation, however, is the very reason why labour rights have to be negotiated internationally. Existing voluntary international standards of the UN, ILO or OECD are useful but not sufficient, and trade sanctions in the WTO framework pose dangers of disguised protectionism. More promising but still imperfect avenues are Free Trade Agreements that could be used to enforce minimum ILO labour standards and transparent certifications, e.g. for fair trade products.
Keywords: F13; J81; O24; 330; Internationale Arbeitsteilung; Arbeitsbedingungen; Sozialstandards; Handelsabkommen; Exportbeschränkung; Multinationales Unternehmen; Arbeitsproduktivität; Asien